Estudo comparativo de isolados de Cercospora coffeicola: análises moleculares, bioquímicas e processo infeccioso na interação com cafeeiro - Andrade, Camila Cristina Lage de (2015)
There are few studies on different symptoms of the “common” and the “black” brown eyespot (BE), in field conditions.Thus, the goals this study were 1) characterize strains by phylogenetic studies, to assess the cercosporin production in vitro, aggressiveness and distribution of nutrients in the leaves infected by strains; 2) to assess the reproducibility of lesion type of the “common BE” and the “black BE” disease in greenhouse conditions, through infection process using scanning electron microscopy and quantitative RT-PCR; 3)to investigate whether the biochemical defense response in coffee leaves is similarly induced by the common BE and the black BE. The first study, eight strains were collected from different regions of Brazil and were inoculated in two coffee cultivars under greenhouse conditions. Based on the nucleotide sequence of the elongation factor genes and actin, it was observed that the isolates used in phylogenetic studies grouped into one similar group to the C coffeicola. It was observed that there was difference in the incubation period, area under the curve of disease severity and cercosporin production in vitro regardless of the lesion induced by strains. From these results, it can be suggested that there is difference in virulence between the strains. The distribution of mineral nutrients in the leaf tissue of symptomatic and asymptomatic coffee plants of was accessed through X-ray microanalysis of leaf fragments. There was a nutrient distribution gradient for: calcium, potassium, magnesium and phosphorus independent of the type of lesion type induced each of the eight strains. In this second study, there was no difference between the two strains for germination, penetration, colonization, and lesion formation. Both strains were able to induce the expression of the four defense-related genes in coffee leaves; however there was variation in the timing of expression for each strain depending on the gene and on the endogenous control used in this study. All the lesions observed in t he greenhouse were of the common BE type. In the third study, it was observed that activated the two strains peroxidase, catalase, superoxide dismutase, ascorbate peroxidase and phenylalanine ammonia lyase involved in metabolism antioxidant similarly coffee leaves. Other research should be conducted to investigate the questions raised by these studies. Other factors possibly environmental and nutritional, or even some genetic variability among strains may be involved with the occurrence of different symptoms observed.